An Inactivated West Nile Virus Vaccine Candidate Based on the Lineage 2 Strain - Mikhail F. Vorovitch; Ksenia K. Tuchynskaya; Yuriy A. Kruglov; Nikita S. Peunkov; Guzal F. Mostipanova; Ivan S. Kholodilov; Alla L. Ivanova; Maria P. Fedina; Larissa V. Gmyl; Evgeny S. Morozkin; German V. Roev; Lyudmila S. Karan; et al. (Vaccines)
Background: West Nile virus (WNV) is a rapidly growing problem worldwide. The lack of emergency treatment and a safe licensed vaccine against WNV allows the virus to cause sporadic outbreaks of human disease, including fatal cases. Formalin-inactivated vaccines have been used for a long time and have been shown to be very safe and effective, especially in susceptible populations. Methods: By adapting tick-borne encephalitis vaccine production technology, we produced a laboratory-inactivated vaccine against WNV based on the strain SHUA, isolated from humans with a lethal WNV infection in the year 2021. Results: The potential vaccine was tested for safety in vitro and in vivo in outbred SHK mice of different ages, including PCR analysis of the brains of these mice to test for the absence of viral RNA after intracerebral injection. Conclusions: The inactivated whole-virion laboratory vaccine showed 100% seroconversion and immunogenicity against WNV strain SHUA-1, isolated from a lethal human case, and provided the mice with 100% protection from disease and death.